Epstein-Barr virus (EBV) nuclear antigen (EBNA)-4 mutation in EBV-associated malignancies in three different populations - Chu, P. G.; Chang, K. L.; Chen, W. G.; Chen, Y. Y.; Shibata, D.; Hayashi, K.; Bacchi, C.; Bacchi, M.; Weiss, L. M. (Amer Soc Investigative Pathology, Inc, 1999)
Different ethnic groups with a high human leukocyte antigen (HLA)-A11 prevalence have been shown to experience a high rate of Epstein-Barr virus (EBV) infection, EBV-associated malignancies, and Epstein-Barr nuclear antigen (EBNA)-4 mutations. The epitopes 393-408 and 416-424 of EBNA-4 are major antigenic epitopes that elicit an HLA-A11 cytotoxic T lymphocyte (CTL) response to EBV infection. Mutations selectively involving one or more nucleotide residues in these epitopes affect the antigenicity of EBNA-4, because the mutant EBV strains are not recognized by the HLA-A11-restricted CTLs. To investigate these mutations in common EBV-associated malignancies occurring in different populations, we studied the mutation rate of epitopes 393-408 and 416-424 of EBNA-4 in 25 cases of EBV-associated Hodgkin's disease (HD), nine cases of AIDS-related non-Hodgkin's lymphoma, and 37 cases of EBV-associated gastric carcinoma (GC) from the United States, Brazil, and Japan. We found one or more mutations in these two epitopes in 50% (6/12) of United States HD, 15% (2/13) of Brazilian HD, 50% (6/12) United States GC and 28% (7/25) Japanese GC, and 22% (2/9) of United States AIDS-lymphoma. Similar mutations were found in 30% (3/10) of United States reactive, 0% (0/6) of Brazilian reactive, and 25% (2/8) Japanese reactive tissues. The most frequent amino acid substitutions were virtually identical to those seen in previously reported isolates from EBV-associated nasopharyngeal carcinomas and Burkitt's lymphomas occurring in high prevalence HLA-A11 regions. However, only 2/28 (7%) mutations occurred in HLA-A11-positive patients. Our studies suggest that: 1) EBNA-4 mutations are a common phenomenon in EBV-associated HD, GC, and AIDS-lymphoma; 2) the mutation rate does not vary in these geographic areas and ethnic groups; 3) EBNA-4 mutations in EBV-associated United States and Brazilian HD, United States and Japanese GC, and United States AIDS lymphomas are not related to patients' HLA-A11 status.